Family Well-Being Under Pressure: Rhythmanalysis Applied to Post Pandemic Family Dynamics - Gucciardo, Gaetano; Siino, Marianna (Italian Sociological Review, 2022)
This contribution deals with the centrality of family relationships for the production of individual well-being, both on a cognitive level, i.e. as an influence on satisfaction with one’s own life and, therefore, as the outcome of a cognitive evaluation, and on an experiential and emotional level, i.e. as an influence on moment-to-moment experience. It starts from an analysis of subjective well-being, arriving at a concept of relational well-being, whilst proposing an approach of rhythmanalysis as a tool for understanding the changes occurring in family dynamics in the post-Covid era.